Pengaruh Lama Fermentasi Biofertilizer terhadap Pertumbuhan Tinggi Batang Tanaman Kangkung (Ipomoea reptans) dalam Sistem Hidroponik - Nurhayani H. Muhiddin; akhmad Syakur; putri damayanti; sahrani U (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to determine the effect of biofertilizer fermentation duration on the stem length growth of water spinach (Ipomoea reptans) in a hydroponic system. The biofertilizer was fermented for 7, 14, and 21 days, then combined with AB mix nutrient solution in various concentrations. The experimental design used was a Randomized Block Design (RBD) with five treatments: 100% AB mix control, biofertilizer combined with 75%, 50%, and 25% AB mix, and biofertilizer without AB mix, with three replicates for each fermentation duration. The parameter observed was the stem length of water spinach plants after five weeks of cultivation. The results showed that the biofertilizer from the 21-day fermentation had the most significant effect on stem length increase, particularly in combination with 50-75% AB mix. Meanwhile, the use of biofertilizer without AB mix resulted in shorter stem lengths. Thus, the biofertilizer from the 21-day fermentation process has potential as a nutritional supplement in hydroponic systems, but it cannot fully replace the role of AB mix.